2016
DOI: 10.1016/j.athoracsur.2015.12.069
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Operative Experience of Cardiac Surgical Trainees: What Are Residents Really Doing in the Operating Room?

Abstract: There is pronounced heterogeneity in the cardiac operative experience of cardiothoracic surgical residents in the United States, with only CABG and AVR routinely performed by graduating residents as the operative surgeon. This heterogeneity may lead to insufficient training in certain procedures for many graduates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…Our findings are in agreement with those of Shah and colleagues [10], who demonstrated significant heterogeneity in residents' CT surgical operative experiences on the basis of residents' interest alone. In that study, residents who had a primary interest in thoracic surgery performed substantially fewer cardiac operations than their counterparts who were interested in cardiac surgery [10].…”
Section: Commentsupporting
confidence: 93%
“…Our findings are in agreement with those of Shah and colleagues [10], who demonstrated significant heterogeneity in residents' CT surgical operative experiences on the basis of residents' interest alone. In that study, residents who had a primary interest in thoracic surgery performed substantially fewer cardiac operations than their counterparts who were interested in cardiac surgery [10].…”
Section: Commentsupporting
confidence: 93%
“…Adequate preparation is best achieved by supervised autonomy in training; however, it is not clear this is routinely achieved. Shah and colleagues [8] surveyed graduating thoracic surgery residents and found that residents routinely performed only two of 13 cardiac operations to the extent that they described themselves as the operating surgeon.…”
Section: Commentmentioning
confidence: 99%
“…Also, a given rotation may entail significantly different clinical and operative experience depending on the institution and year within the program. Although this was not specifically examined in the present study, a previous study based on 2015 TSRA/TSDA ITE data specifically examined the operative experience for both traditional and integrated residents throughout the duration of their training program [7].…”
Section: Commentmentioning
confidence: 99%